2009
DOI: 10.1177/159101990901500311
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Nucleolysis for Management of Pain and Disability in Prolapsed Lumber Intervertebral Disc

Abstract: The prevalence rate of low back pain in a number of studies ranged from 22% to 65% in one year, and lifetime prevalence ranged from 11% to 84%. Over the years many percutaneous minimally invasive therapeutic modalities have evolved. Intradiscal oxygen-ozone therapy has also showed promising results. We undertook a prospective cohort study to evaluate the therapeutic outcome of oxygen-ozone therapy on patients with lumber disc herniation in the Indian population. After obtaining ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 10 publications
(9 reference statements)
4
31
0
1
Order By: Relevance
“…e reduction of VAS score from baseline with in four weeks following treatment was 8.0±1.63 to 0.30±0.95. G das et Al 12 found that the reduction of VAS score from baseline to three weeks following treatment was 7.58 ±86 to 2.75 ±1.42 which was similar to present study.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…e reduction of VAS score from baseline with in four weeks following treatment was 8.0±1.63 to 0.30±0.95. G das et Al 12 found that the reduction of VAS score from baseline to three weeks following treatment was 7.58 ±86 to 2.75 ±1.42 which was similar to present study.…”
Section: Methodssupporting
confidence: 90%
“…40% was male, 60% was female and male: female ratio was 2:3. G das et Al 12 found that Patients range of age was 21-65 (average 46.04) years which was closely resembles the present study. 50% were housewife, 20% was businessmen, 10% was student, 10% was labour and 10% was sedentary worker in private job.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Pain perception was reduced after the subsequent treatments were delivered. Several past investigators (10)(11)(12)(13)(14) had also noted the same thing. On the other hand, it is observed that under both the treatments, the average VAS scores reduce substantially after 3 rd week, which are in agreement with the findings of Muto and Avella (10) and Das et al (11) .…”
Section: The Study and The Collected Datamentioning
confidence: 61%
“…A few recent papers (7)(8)(9) reveals role of ozone in inflamatory, vascular as well as compressive factors which are responsible for pain. Although studies of effect of ozone Neucleoplasty and physiotherapy separately on low back pain has proven to be effective in chronic low back pain (7)(8)(9)(10)(11)(12)(13)(14)(15) , we did not come across any data evaluating both the approaches in a single study. …”
Section: Introductionmentioning
confidence: 99%